PENDATAAN KEBUTUHAN DAN PEMAHAMAN SEKOLAH SIAGA BENCANA KECAMATAN BAITUSSALAM ACEH BESAR (STUDI KASUS SMP NEGERI 1) - Ichsan .; Niswanto .; Ibnu . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
The problem in this study is how the availability of community facilities and infrastructure at SMP Negeri 1 Baitussalam Aceh Besar schools in the face of the tsunami disaster, how the school community's preparedness, and how the concept of the school into tsunami disaster prepared schools. This study aims to determine the needs of facilities and infrastructure and the level of community knowledge, as well as preparing the concept of disaster preparedness school in SMP Negeri 1 Baitussalam Aceh Besar to tsunami disaster. This research is a qualitative descriptive research. Data in this research use primary data and secondary data. The population used in this study is the entire community of SMP Negeri 1 Baitussalam Aceh Besar consisting of principals, vice principals, heads of administration, and staff of teachers and school guards, cafeteria attendants, and students. The sample was taken as many as 68 people in Stratified Sampling. Data collection was done by observing, distributing and distributing questionnaires to the school community using the percentage formula. The results will be univariatally analyzed to prepare the concept of disaster prepared schools. Based on the results of research, the availability of facilities and infrastructure of the school community in the face of tsunami disaster using measurement parameter and preface of disaster preparedness school, there are several items that must be completed, including the availability of logistics reserves. While the level of knowledge of the school community is in good category. To that end, the concept needed to make the disaster alert school is the school must complete the deficiencies that have been recorded to make the school into a disaster alert school.Keywords: preparedness, needs, school disaster preparedness